2023
DOI: 10.1007/s10705-023-10268-y
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of phosphate-solubilizing bacteria improves soil phosphorus mobilization and maize productivity

Abstract: Phosphate-solubilizing bacteria represent a bioalternative in making soil-immobilized phosphorus (P) available to plants, and consequently improve agriculture sustainability and reduce nutrient pollution. In this study, we examined whether Rhizobium sp. B02 inoculation can affect the soil P fractions. Moreover, we investigated how inoculation influences the growth, physiological traits, and productivity of the maize crop. Field tests were carried out to evaluate the combined application of strain B02 and reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
4
0
1
Order By: Relevance
“…In response to this problem, this study demonstrated the potential of PSB inoculation with different P sources to improve soil P lability, thus transforming insoluble forms of P into usable forms for Kikuyu grass, and in turn reducing the application of synthetic fertilizers. Preliminary studies have shown that PSB inoculants improve soil P dynamics and promote soil P legacy circularity [ 25 , 26 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to this problem, this study demonstrated the potential of PSB inoculation with different P sources to improve soil P lability, thus transforming insoluble forms of P into usable forms for Kikuyu grass, and in turn reducing the application of synthetic fertilizers. Preliminary studies have shown that PSB inoculants improve soil P dynamics and promote soil P legacy circularity [ 25 , 26 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results coincided with the higher acid phosphomonoesterase activity ( Figure 5 ) and the higher availability of P and P in the labile fraction of the soil. Beltran et al [ 38 ] found a greater availability of P in the labile fractions with the inoculation of Rhizobium sp., improving growth and development in annual forage crops and P nutrition, in turn allowing a reduction in the application of mineral P fertilizers to 50%. The synergism between PSB inoculation and low-solubility P sources increased dry matter accumulation in Kikuyu grass relative to high-solubility mineral sources.…”
Section: Discussionmentioning
confidence: 99%
“…ECM fungi can mobilize P, in uence host plant growth and P uptake [45], [46], and provide nutrients for Przewalski horses in the Hustai area. On the other hand, phosphate-solubilizing bacteria able to improve soil phosphorus mobilization increasing labile Pi [47].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the capacity of some microbes to release soluble P from insoluble forms can positively affect plant growth. Inoculation of Rhizobium in non-leguminous plants, for example, resulted in an increased transformation of P from unavailable to available forms in soil, thereby enhancing plant nutrition [10]. Co-inoculation of strains possessing multiple PGP traits, therefore, has the potential to improve nutrient utilization.…”
Section: Introductionmentioning
confidence: 99%